Growth kinetic and fuel quality parameters as selective criterion for screening biodiesel producing cyanobacterial strains. (January 2018) - Gayathri, Manickam; Shunmugam, Sumathy; Mugasundari, Arumugam Vanmathi; Rahman, Pattanathu K.S.M.; Muralitharan, Gangatharan
Highlights: Fourteen cyanobacterial strains were screened based on growth kinetic parameters. Biochemical characters like total carbohydrate, reducing sugar and protein content were also analyzed. The selected five strains was evaluated for biodiesel quality parameters based on FAME profile. Selection process includes MCDA-PROMETHEE-GAIA analysis. Nostoc spongiaeforme MBDU 704 was selected as the most suitable strain for biorefinery. Abstract: The efficiency of cyanobacterial strains as biodiesel feedstock varies with the dwelling habitat. Fourteen indigenous heterocystous cyanobacterial strains from rice field ecosystem were screened based on growth kinetic and fuel parameters. The highest biomass productivity was obtained in Nostoc punctiforme MBDU 621 (19.22 mg/L/day) followed by Calothrix sp. MBDU 701 (13.43 mg/L/day). While lipid productivity and lipid content was highest in Nostoc spongiaeforme MBDU 704 (4.45 mg/L/day and 22.5% dwt) followed by Calothrix sp. MBDU 701 (1.54 mg/L/day and 10.75% dwt). Among the tested strains, Nostoc spongiaeforme MBDU 704 and Nostoc punctiforme MBDU 621 were selected as promising strains for good quality biodiesel production by Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) and Graphical Analysis for Interactive Assistance (GAIA) analysis.